Penyuluhan Hukum Tentang Tindak Kekerasan Dalam Rumah Tangga Bagi Pengurus Tim Penggerak PKK Di Kecamatan Air Batu Kabupaten Asahan - Siti Ameliyah, Syahrul, Mhd. Abduh Isma, Adnan Buyung (Pusdikra Publishing, 2023)
Violence, especially domestic violence, is a violation of human rights and a crime against human dignity and is a form of discrimination. Violence in any form and for any reason is a form of crime that cannot be justified. Therefore, no matter how small the violence committed can be reported as a crime that can be processed by law. Domestic violence (KDRT) is any act against a person, especially women, which results in physical, sexual, psychological misery or suffering, and neglect of the household including threats to commit acts, coercion, or unlawful deprivation of liberty within the household sphere. The enactment of Law Number 23 of 2004 by the government has changed the perspective, practicing religious teachings, all religions have good goals, none of the religions teach violence, so when religion becomes the foundation in a family, domestic violence will be avoided. Communication within the family must be built properly every day, which can be started from trivial things such as saying goodbye, in good communication there is openness to each other which causes a sense of mutual understanding and mutual trust to emerge which can become the foundation for solving problems. Education From an early age children are taught not to hit, not to say harshly, to how to deal with anger. Education from an early age is expected to shape the character of children who will be carried and applied to adulthood. Counseling About Domestic Violence. The government has a positive legal product in the form of a domestic violence abolition law which can be disseminated to the aus community so that people can better understand the impact and avoid domestic violence. So far, violence has occurred due to a lack of communication and commitment within a family to respond to the dynamics/problems of life, women and children are often the victims. In this social work perspective, the focus of social work is to play a role in efforts to help/assist in the recovery of victims who tend to have an impact on the psyche which certainly hinders their social relations and functioning, so that the role of social workers in assistance is very much needed in accordance with the mandate of Article 10 regarding the rights of victims and legal assistance at every level of the examination process in accordance with the provisions of laws and regulations. Impact on Physical and Mental Health Domestic violence can be in the form of physical violence that causes injuries such as; bruises, headaches to broken bones. Women also need to have education to be able to face problems and solve problems and have the right solution for all. Mothers give in more and solve problems with full maturity and level-headedness.